The prevalence of postoperative symptoms within 24 hours after ambulatory surgery in a University Hospital. - Adlin Dasima AK,; Karis M, (Department of Surgery, UKM Medical Centre, 2013)
Ambulatory surgery has now becoming increasingly popular and it is generally well accepted. Major complications following ambulatory surgery are very rare but certain postoperative symptoms can be very unpleasant and distressing to the patients. Follow-up phone calls regarding their well being at home following the surgery may give us the clue and allow us to identify certain problems that can be sorted out immediately or as a reference for a better service in future. The present study was carried out to determine the prevalence of common postoperative symptoms and their subsequent effects within 24 hours after ambulatory surgery by follow-up phone calls. We prospectively studied 199 ASA I and II patients, but only 187 patients were analyzed. Patients had undergone general surgery, orthopaedic, urology, gynaecology or ear, nose and throat (ENT) surgery. Pain was scored based on Numerical Rating Scale (NRS). Majority of patients (70.8%) had only mild pain prior to discharge home. At 24 hours postoperatively, pain was the commonest symptom reported (92.5%) followed by sleepiness (72.2%), dizziness (49.7%), sore throat (17.1%), nausea and vomiting (7.5%) and headache (7%). Sleep was mildly affected in nearly 50% of the patients. Fifty seven percent of patients did not need assistance in performing daily activities during the 24 hours, post surgery. Majority of patients were satisfied (81.3%) with ambulatory surgery. In conclusion, pain was the commonest postoperative symptom encountered following the surgery. Sleep was mildly affected by the postoperative symptoms. Most of the patients did not need assistance in performing their daily activities following surgery. All patients were able to return to at least more than 50% of their normal daily activities at 24 hours after the surgery. Overall satisfaction towards ambulatory surgery was good.